(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The data of the captures with sticky traps, baited with sexual pheromone of Eupoecilia ambiguella and the heat accumulation are used to forecast the starting moment and the pattern of emergency of moths from the cocoon. The data have been collected between 1982 and 1987 in the vine growing areas of Arda and Tidone Valleys, in Piacenza province, and Versa Valley, near Pavia (Northern Italy). During the first annual flight period the E. ambiguella behaviour has resulted uniform in the three areas with a similar quantity of degree-days required to complete the different phases of the flight pattern. There is the possibility to have a third flight when during the second half of the second flight there is average heat accumulation of more than 13 degree-days ( calculated using Allen method from the 1st January with a lower threshold of development of 10°C). It has been calculated the regression line between the percentage of catches and the thermal sum, obtaining for all the flights highly significant correlation coefficients. The evolution of the flights forecasted in these lines adaptes well to the real data, particularly for the first and the second flight.